Menapak Jejak Seni Gambuh dalam Naskah-Naskah Panji Melayu - Priyo Joko Purnomo; Wahyudhi Wahyudhi (Perpustakaan Nasional RI, 2020)
Gambuh as the performing art in Malay area became one of the cultural transformation evidences of the close relation between Java and Malay. The history of gambuh performance in Malay area recorded in the archipelago’s manuscripts, one of them is a manuscript entitled Surat Gambuh which is being the collection of Leiden University Library. This paper attempts to examine the contents of the manuscript in order to reconstruct the gambuh performance art in Malay and also trace the historical aspects. As far as the research had been done, there have been no studies of this manuscript so it is necessary to first transliterate it using a critical method. Furthermore, the historical aspects are explored using a historical approach by adding data from other texts of Panji. The analysis result of the reflection of Malay gambuh performance rules and historical aspects show that there is a transformation of work from oral tradition to written tradition, the cultural acculturation between Java and Malay, and the Islamic influence behind Malay gambuh.